Photographs of Old Wehe Family Photographs - Watkins, Howard::::::::: (1983)
Carl Edwin Wehe, Mary Wehe, and W. Schuyler Wehe with mother Lottie Sisson Wehe Original photograph taken 1898 by Lewis Edwin Wehe